Labio doble congénito asociado a hemangiomas: A propósito de un caso - Costa Hanemann, João Adolfo; Tostes Oliviera, Denise; Fernandes Gomes, Mônica [UNESP]; Da Silva Dos Anjos, Mário James; Sant'Ana, Eduardo (My University, 2004)
Double lip is a developmental abnormality which may occur either isolated or as a component of Ascher's syndrome. A case of congenital double lip associated to hemangiomas and enlargement of the thyroid is reported. The oral and facial hemangiomas were excised under local anesthesia. Surgical reconstruction of the upper lip was done in order to reduce the interference with speech and mastication. The recognition and treatment of the abnormalities are discussed.
Congenital double lip associated to hemangiomas: Report of a case
Keywords: Ascher's syndrome; Double lip; Hemangioma; aged; ascher syndrome; blepharochalasis; cancer surgery; case report; clinical feature; congenital double lip; congenital malformation; diagnostic accuracy; disease association; follow up; goiter; hemangioma; human; lip reconstruction; local anesthesia; male; mastication; mouth malformation; speech; symptom; syndrome